Pediatric anterior cruciate ligament injury: A focus on prevention and treatment in the young athlete (Clinics in Sports Medicine, 2011)
Das gesamte Heft 4/2011 der Zeitschrift beschäftigt sich mit dem Thema Kreuzbandverletzungen bei Sport treibenden Kindern.